E-procurement associado a MRO: o caso Caixa Econômica Federal - Bordignon, Gerson (2003)
The evolution of Information Technology (IT) - principally the Internet - from the academic realm to the business arena has generated discussions concerning the impact of this process on existing business models. The Brazilian government has been working to adjust its legal framework in order to take advantage of the benefits the new business environment offers the public sector. The primary objective of this study is to identify the benefits accruing to the Caixa Econômica Federal, in terms of improved efficiency, from the implementation of its online shopping site, MRO (maintenance, repair and operation). Using a simplified case study methodology, an analysis of the strategic importance of the implementation of the Caixa Econômica Federal' 5 shopping site is provided, specifically focused on how the relevant technological, organizational, and cultural' aspects have influenced the efficiency of the institution's productive processes. While the results obtained are significant with respect to investmentrecovery time, and promising in terms of the possibilities they offer for reducing the institution's administrative costs, of greater relevance is the site's potential as a mechanism for adding value to the bank's financiai performance. In this context, the Caixa Econômica Federal's challenge is to wed the market opportunities arising from the expertise that has been acquired to the idle capacity generated by productivity gains, and, in this way, to develop a product that provides vast revenue generating potential.